2018
DOI: 10.1007/s13197-018-3427-0
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, morphological and functional properties of protein isolates obtained from four fish species

Abstract: In this study, we investigated the physicochemical, morphological and functional characteristics of fish protein isolates (FPIs) prepared from four fish species through alkali solubilization and isoelectric precipitation. Significant differences were observed in the protein content, physicochemical, morphological and functional characteristics among FPIs. Morphology and particle size analysis revealed a significant difference in the shape and size of FPIs. Lipid oxidation of FPIs varied between 0.206 and 0.305… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 33 publications
2
17
1
Order By: Relevance
“…The API bulk density value was lower than that of isolate protein from rainbow trout (0.58±0.01 g/mL) and catfish (0.64±0.01 g/mL) (Lone et al, 2015;Haryati et al, 2020). However, it was higher than the protein isolate from Indian mackerel (0.31±5.12 g/mL), pony fish (0.27±8.12 g/mL), and sardine (0.36±5.32 g/mL) (Kumarakuru et al, 2018). Flour generally has a bulk density ranging from 0.37-0.77 g/mL (Akinwale et al, 2017).…”
Section: Physical Properties Of Api Bulk Densitymentioning
confidence: 82%
See 1 more Smart Citation
“…The API bulk density value was lower than that of isolate protein from rainbow trout (0.58±0.01 g/mL) and catfish (0.64±0.01 g/mL) (Lone et al, 2015;Haryati et al, 2020). However, it was higher than the protein isolate from Indian mackerel (0.31±5.12 g/mL), pony fish (0.27±8.12 g/mL), and sardine (0.36±5.32 g/mL) (Kumarakuru et al, 2018). Flour generally has a bulk density ranging from 0.37-0.77 g/mL (Akinwale et al, 2017).…”
Section: Physical Properties Of Api Bulk Densitymentioning
confidence: 82%
“…Flour generally has a bulk density ranging from 0.37-0.77 g/mL (Akinwale et al, 2017). Bulk density can be influenced by protein microstructure, particle size, the intensity of the attractive forces between particles, manufacturing method, drying procedure, and moisture content (Lone et al, 2015;Kumarakuru et al, 2018). According to Foh et al (2012), the small bulk density is suitable for the formulation of weaning foods.…”
Section: Physical Properties Of Api Bulk Densitymentioning
confidence: 99%
“…In addition, the particle size of albumin and glutelin makes them better protein fractions in terms of promising functional properties than prolamin and globulin. It has been reported that smaller particle size promotes the dissolution rate of protein in the aqueous phase, which results in better functional properties ( Kumarakuru, Reddy, & Haripriya, 2018 ). However, as the quantity of glutelin was very low, the functional properties of albumin derived from banana peel were found significantly promising and advantageous among all the protein fractions.…”
Section: Resultsmentioning
confidence: 99%
“…However, these findings are not in line with the size determined by light scattering, which might be due to the formation of soluble protein aggregate in the aqueous solution, which measured the average hydrodynamic size of the aggregate ( Xiong et al, 2018 ). Nevertheless, the smaller particle size of glutelin with rough and flattened microstructure promoted the dissolution rate in the aqueous phase and resulted in higher foaming capacity and dispersibility value Kumarakuru et al (2018) . In contrast, the smooth and homogeneous morphology of albumin was responsible for increased WHC, OHC, and EC ( Mao & Hua, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…Isolated proteins from there different fish roes, including halibut, skipjack tuna, and yellowfin tuna treated by ISP processing have been demonstrated to have good emulsifying activity (Lee et al., 2017). Moreover, the comparison of functional properties of protein isolates from catfish ( Batrachocephalus mino ), Indian mackerel ( Rastrelliger kanagurta ), ponyfish ( Aurigequula fasciata ), and sardine ( Sardinella brachysoma ) and protein isolates from salmon, cod, and herring by‐products have also been reported by Kumarakuru, Reddy, and Haripriya (2018) and Abdollahi and Undeland (2019), respectively. Therefore, the comparison within isolated proteins from three different species of sea urchin is essential to develop novel functional biomaterials in food system.…”
Section: Introductionmentioning
confidence: 81%